A Height-Based Dosing Algorithm of Bupivacaine in Spinal Anesthesia for Decreasing Maternal Hypotension in Cesarean Section Without Prophylactic Fluid Preloading and Vasopressors: A Randomized-Controlled Non-Inferiority Trial - Huang, Qiang; Wen, Gengzhi; Hai, Chao; Zheng, Zihao; Li, Yali; Huang, Zengping; Huang, Bowan (Frontiers in Medicine, 2022)
Background: There is a high incidence of maternal hypotension in spinal anesthesia for caesarean section. This study aims to investigate whether there is a height based dosing algorithm of bupivacaine that provides adequate anesthesia with less maternal hypotension. Methods: Two hundred and eighty parturients without prophylactic fluid pre-loading were divided into two groups: Test and Conventional group. In Test group, a height based dosing algorithm was used to confirm the dose of bupivacaine in parturients without prophylactic vasopressors. In Conventional group, a constant dose of bupivacaine was used. The complications and quality of anesthesia were evaluated. Results: In Conventional group, the shorter participants had higher incidence of hypotension, faster sensory block time, and more participants with complete motor block (P = 0.030, 2.957×10-14, and 0.012). In Test group, the incidence of hypotension, sensory block time, and number of participants with complete motor block did not change with height (P = 0.199, 0.617, and 0.209). The height based dosing algorithm of bupivacaine decreased the incidence of hypotension (P = 0.004), induced lower sensory block level and less degree of motor block (P = 3.513×10-7 and 5.711×10-11). The quality of analgesia, quality of muscle relaxation and degree of intraoperative comfort were similar in both groups (P = 0.065, 0.498 and 0.483). Conclusions: The height influences the dose of bupivacaine in spinal anesthesia; without prophylactic fluid pre-loading and vasopressors, the height based dosing algorithm of bupivacaine is suitable, and meets the caesarean section’ requirement with less maternal hypotension. Clinical Trial Registration: ClinicalTrials.gov (NCT03497364). (https://register.clinicaltrials.gov/prs/app/template/EditProtocol.vm?listmode=Edit&uid=U0002HUB&ts=3&sid=S0007 VR4&cx=dpubw9)